Does food market modernisation lead to improved dietary diversity and diet quality for urban Vietnamese households?1. (21st May 2019) - Rupa, Jesmin Ara; Umberger, Wendy J.; Zeng, Di
Abstract : This study investigates the possible mechanisms through which modern food markets may affect Vietnamese households' dietary diversity and diet quality using data from a survey of 1, 700 urban households with seven‐day food recall. We calculate Household Dietary Diversity Scores to measure dietary diversity, and use consumption frequencies of micronutrients (vitamin A and heme iron) and a macronutrient (protein) to create a household measure of diet quality. We estimate a Poisson regression model using a two‐step control function approach to address the potential endogeneity of our key explanatory variable, modern market food expenditure shares. Higher modern market food expenditure share is positively and significantly associated with consumption frequency of heme iron, but there are no significant associations with consumption of vitamin A and protein. We further explore indirect linkages between food expenditure shares and dietary diversity, which in turn, may be linked to household diet quality. Results from a system of equations show that the food expenditure share variable has no significant relationship with dietary diversity, but dietary diversity is positively and significantly associated with diet quality. Our results indicate that alone, policies which encourage 'food market modernisation' are not enough to improve diet quality in urban Vietnam.